2022
DOI: 10.1021/acssuschemeng.2c00632
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Burst Synthesis of High-Performance Si Nanotube Sheets for Lithium-Ion Batteries

Abstract: One of the drawbacks of Si-based battery anodes is poor cycle stability due to volume expansion of the anode material. To overcome this limitation, we propose a novel strategy of Si nanotube sheet synthesis using the thermal burst method. Herein, SiO 2 nanotubes are prepared using the hard template method; subsequently, Si nanotube sheets are produced during the thermal burst caused by magnesiothermic reduction, which occurs because nanotubes are broken by ZnO with a larger thermal expansion coefficient. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The carbon source dopamine hydrochloride (DH) contains the elements N and Cl. In the current study, we discover that Cl is not involved in the reaction with DH as the carbon-coating precursor. However, we carefully analyzed the XPS results in some articles , and found that there is a peak at approximately 200 eV in the XPS full spectrum, which is the peak of Cl according to the literature. , Despite the fact that their XPS spectrum shows a peak of Cl, their analysis makes no mention of it.…”
Section: Introductionmentioning
confidence: 59%
“…The carbon source dopamine hydrochloride (DH) contains the elements N and Cl. In the current study, we discover that Cl is not involved in the reaction with DH as the carbon-coating precursor. However, we carefully analyzed the XPS results in some articles , and found that there is a peak at approximately 200 eV in the XPS full spectrum, which is the peak of Cl according to the literature. , Despite the fact that their XPS spectrum shows a peak of Cl, their analysis makes no mention of it.…”
Section: Introductionmentioning
confidence: 59%
“…The five fitting peaks at 282.89, 284.81, 285.62, 288.43, and 289.74 eV in the high-resolution XPS of C 1s (Figure 5b) correspond to C−Si, C−C, C−N, C−O, and C�O, respectively. 9,[15][16][17][18][19][20][21]46 The presence of the C−N-conjugated bond proves that N atoms have been doped into the carbon layer. The diffraction peak in the high-resolution XPS of N 1s (Figure 5c) could be fitted to three peaks: pyridinic N at 398.34 eV, pyrrolic N at 400.91 eV, and graphitic N at 403.28 eV.…”
Section: Characterizationmentioning
confidence: 99%
“…7 However, Si anodes undergo a significant volume change (∼300%) during the lithiation/delithiation process, 8−10 leading to internal stress and various problems with active substance falling off the collector, instability of the solid electrolyte interface (SEI) layer, failure of the electrical connection between the active substance and the collector, and a decrease in battery capacity, conductivity, and cycle life. 11−15 To address these issues, many excellent studies have been reported, including the preparation of Si nanoparticles, 8,16 nanorods, 17 nanowires, 18 and nanotubes, 19 the development of active-inertia systems, and the construction of porous structures. 5,20−25 Among these, reducing the particle size can stabilize the performance of Si anodes, but significant internal stress accumulates during multiple charges and discharges, eventually leading to battery failure.…”
Section: Introductionmentioning
confidence: 99%
“…are combined with TiO 2 in order to boost the electronic conductivity of anode materials. 14–16 Zhang et al 17 prepared carbon-coated TiO 2 employing surfactant as the carbon source. After 500 cycles, the capacity is 201.3 mAh g −1 at 1 C (1 C = 168 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: jbchen@gzu.edu.cn b Collaborative Innovation Center of Guizhou Province for Efficient Utilization of Phosphorus and Fluorine Resources, Guizhou University, Guiyang 550025, China tronic conductivity of anode materials. [14][15][16] Zhang et al 17 prepared carbon-coated TiO 2 employing surfactant as the carbon source. After 500 cycles, the capacity is 201.3 mAh g −1 at 1 C (1 C = 168 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%